(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
The evolution of the foredeeps which developed on the northern Adriatic foreland took piace in a regime of oblique convergence. From the Late Oligocene onwards much compression in the Southern Alps must have been the compressional component of dextral transpression along the Insubric Line, as suggested by the en-échelon arrangement of Neogene thrusts relative to the Insubric Line itself. Diachronous deformation within the Southern Alps, with eastward lateral accretion of the thrust belt, matches diachronous movements along the Insubric Line, where transpression and transtension along the eastern segment seem to outlast movements along the western segment. The age of the Neogene sinistrai displacement along the Giudicarie fault system is in good agreement with that required to accomodate continued thrusting in the eastern block after the termination of thrusting in the western block.